Establishment Of The Asset Confiscation Law To Minimize Corruption In Indonesia - Hudjolly Hudjolly; Rabith Madah Khulaili Harsya; Fatima Suatrat; Kalijunjung Hasibuan; Deny Susanto (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research is qualitative research with a descriptive approach, namely describing a number of things that are closely related to confiscation of assets in criminal law, criminal acts of corruption, and other things. The data used in this research is secondary data in the form of the Criminal Code, Civil Code, statutory regulations, the official website of the House of Representatives, other credible websites, and so on. The researchers analyzed the data using grammatical and systematic legal analysis techniques, namely interpreting every word in the legislation and connecting it with other secondary data or other related legislation. The result in this article show there are three major urgencies for the presence of the Law on Asset Confiscation in Indonesia, namely to provide instruments that are stricter than the current regulations because in the Criminal Code, asset confiscation is only an additional crime and not the main crime, providing a deterrent effect for corruptors and potential corruptors, and of course minimizing corruption cases in Indonesia. Under existing legal structures, state losses resulting from criminal acts of corruption cannot be recovered. Recovering state losses takes years and may not even be returned at all. What is meant to provide a deterrent effect in this research is to impoverish corruptors, change the nomenclature of words whose nature is emphasized from facultative to imperative, and change its status not only to become an additional crime, but also to become a principal crime. On this basis, researchers are of the opinion that the presence of asset confiscation laws in Indonesia can be effective in minimizing the occurrence of corruption in Indonesia.